Formulation and characterisation of nanosuspensions of BCS class II and IV drugs by combinative method. Issue 4 (3rd March 2016) - Attari, Zenab; Kalvakuntla, Sunethra; Reddy, M. Sreenivasa; Deshpande, Mangesh; Rao, C. Mallikarjuna; Koteshwara, K.B.
Abstract : Drug nanocrystals are known to increase the solubility of Biopharmaceutics Classification System (BCS) class II and IV drugs. SmartCrystals are the second generation nanocrystals with particle size of less than 100 nm and increased the stability and solubility of drug and drug product. The combinative methods adopted for the preparation of SmartCrystals are reported to shorten the processing time to reduce the particle size of the drug. This study was carried out with the aim to prepare nanosuspensions of aprepitant and ibuprofen using two pretreatment methods, precipitation and ball milling in a combination of high-pressure homogenisation (HPH). Ball milling and precipitation resulted in nanosuspensions having a particle size less than 1 µ, which were subjected to high HPH. HPH further led to a reduction in the particle size. However, the precipitation method failed to reduce the size of ibuprofen particles to 1 µ.